CREATIVE APPROACHES IN TEXTILE DESIGN AS AN EFFECTIVE METHODS OF INDIVIDUAL EDUCATION OF STUDENTS - REABENCHI, E.; SIMAC, A. (Art and Design, 2024)
Purpose: we aim to examine the effectiveness of individual work in the professional training of future fashion designers through the creative and technological appropriation and application of modern textile design, identification and systematization of modern models of organizing the independent work of university students. Methodology: comparative-historical and typological methods, a method of formal analysis and, partially, figurative and stylistic, were used to study the subject of research. Results: the article describes the experience and results of the implementation of the curriculum "textiles design" for students of Fashion Design. The method basic of artistic literacy through methods are analyzed and systematized, stimulating the development of critical and creative thinking of future specialists in product creating. The main reasons for the insufficient efficiency of students independent work in the theory and practice of higher education were identified. The application methods had a best impact on the process of formation and development of student’s professional artistic thinking. Scientific novelty consists in the fact that the authors used the methods of individual study in creative realization like a structure for the study and understanding of the modern visual language for the creation of textile design, for formation and development of the professional artistic thinking of the Fashion/ textile design students. Practical significance. Researching the cultural connotations of costumes provides valuable educational opportunities for designers and students to deepen their understanding of cultural history, symbolism, and aesthetics. By engaging in scholarly inquiry and critical analysis, designers can develop a nuanced understanding of cultural contexts and apply this knowledge to their creative practice.